2010
DOI: 10.1038/nature09494
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to human serum amyloid P component eliminate visceral amyloid deposits

Abstract: Accumulation of amyloid fibrils in the viscera and connective tissues causes systemic amyloidosis, which is responsible for about one per thousand deaths in developed countries1. Localised amyloid can also be very serious, for example cerebral amyloid angiopathy is an important cause of haemorrhagic stroke. The clinical presentations of amyloidosis are extremely diverse and the diagnosis is rarely made before significant organ damage is present1. There is therefore a major unmet medical need for therapy which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
223
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(240 citation statements)
references
References 22 publications
(36 reference statements)
8
223
0
7
Order By: Relevance
“…SAP is a major component of amyloid deposits of any type. Antibodies to human SAP were shown to eliminate visceral AA deposits in mice (57). It is critical not to misdiagnose ALECT2 amyloidosis as AL amyloidosis to avoid harmful therapy (20).…”
Section: Prognosis and Treatmentmentioning
confidence: 99%
“…SAP is a major component of amyloid deposits of any type. Antibodies to human SAP were shown to eliminate visceral AA deposits in mice (57). It is critical not to misdiagnose ALECT2 amyloidosis as AL amyloidosis to avoid harmful therapy (20).…”
Section: Prognosis and Treatmentmentioning
confidence: 99%
“…The safety of SAP depletion by CHPHC administration has been recently confirmed in a clinical investigation. 48 We therefore suggest that SAP suppression by chemicals, such as CHPHC, might be a novel direction to enhance the efficiency of DNA immunization in human beings. We also suggest that some special nanomaterials that can prevent DNA vaccines from hSAP binding may be a potential novel adjuvant for human DNA vaccines.…”
Section: Discussionmentioning
confidence: 98%
“…87 The Royal Free group in London recently demonstrated that CPHPC followed by anti-SAP antibodies resulted in a quick removal of almost all AA amyloid from the tissues in mice with AA amyloidosis. 88 If this dramatic effect on amyloid can be replicated in humans, it may lead to a major change in the prognosis for patients with all types of systemic amyloidosis.…”
Section: Current Perspectivesmentioning
confidence: 99%